Análise de microdureza do esmalte e da dentina humanos submetidos ao tratamento clareador com peróxido de hidrogênio em altas concentrações, com ou sem a incorporação de agentes remineralizadores - Torquato, Débora Moreira (2016)
In order to reduce dentinal sensitivity and mineral losses on whitened dental substrates, manufacturers have marketed bleaching agents (BA) with fluoride and/or calcium ions. This study evaluated the effect of BA on tooth structure using Knoop hardness test (KHT). The null hypothesis (H0) was that the hardness of the enamel and dentin would not be affected by the application of the gels. A total of 30 human molar teeth fragments containing enamel and dentin were used, and randomly divided into 6 groups: Group 1 - Control; Group 2 - Pola Office; Group 3 - Whitegold Office; Group 4 - Whiteness HP Maxx 35%; Group 5 - Whiteness HP Blue 35%; and Group 6 - Opalescence Boost. The specimens were subjected to KHT, performing six indentations on enamel and six on dentin (three inicials and three finals), made 24 hours after application of the BA. The hardness values were subjected to analysis of variance (ANOVA) and paired T-test at a 5% significance level. No statistically significant differences were observed (p> 0.05) between the experimental groups, regardless of the evaluated substrate or evaluation period. In addition, the paired T-test showed no reduction of KHT in dentine or enamel to any of the experimental groups. In conclusion, the H0 previously stipulated were not rejected, since the use of different BA with or without the incorporation of fluoride and calcium ions did not result in changes in the enamel or the dentin microhardness.